DESIGN OF LEARNING MATERIALS ON LIMIT FUNCTION BASED MATHEMATICAL UNDERSTANDING - Muchamad Subali Noto; Surya Amami Pramuditya; Yudrick Maulana Fiqri (IKIP Siliwangi and I-MES, 2018)
In learning process, students are currently cannot be separated from learning difficulties, including the study material algebra limit function. It because the level of students' mathematical understanding regarding the material is still quite low. This study aimed to analyze the barriers to student learning, designing learning materials based on the material mathematics understanding algebra limit function is valid, determine teacher intervention during the implementation of learning materials and to analyze barriers to student learning after the implementation of learning materials. This research is a qualitative research study design using the form Didactical Design Research. Stages of research conducted: 1) analysis of the situation didactic before learning, 2) analysis of metapedadidatik and 3) the retrospective analysis. Data collection techniques used were tests, interviews, questionnaires, and documentation. The instrument used was a matter TKPM (Comprehension Mathematical Ability Test), interview, validation sheet materials, and documentation guidelines. Research results obtained are students experiencing obstacle to learning the material limit algebra functions. These obstacles are 1) students' difficulties in relating the material prerequisites to limit problems. 2) students can not write properly limit symbol, 3) students can not apply a limit theorem, 4) students are not able to determine the limit value at one point, and 5) students cannot determine the value of the limit at infinity. Learning materials that have been made have validation level of with very valid criteria. The response was given when the student intervention, generally in accordance with response prediction so that interventions carried out in accordance with the design that has been made. After learning materials student learning obstacles implemented reduced/minimized.